Error Analysis on the Use of “Be” in the Students’ Composition - Rochmat Budi Santosa (IAIN Salatiga, 2011)
This study aims to identify, analyze and describe the structure of the use of some errors in the writing of English sentences in the text and the aspects surrounding the Student Semester 3 of English Department STAIN Surakarta. In this study, the researcher describes the error use of 'be' both as a linking verb or auxiliary verb. This is a qualitative-descriptive research. Source data used is a document that is the writing assignment undertaken by the Students taking Writing course. Writing tasks are in narrative, descriptive, expositive, and argumentative forms. To analyze the data, researcher uses intra lingual and extra lingual method. This method is used to connect the linguistic elements in sentences, especially some of the elements either as a linking verb or auxiliary verb in English sentences in the text. Based on the analysis of error regarding the use of 'be' it can be concluded that there are 5 (five) types of errors made by students; error about the absence (omission) of 'be', error about the addition of 'be', the error on the application of 'be', errors in placements 'be', and a complex error in the use of 'be'. These errors occur due to inter lingual transfer, intra lingual transfer and learning context.keywords; Error Analysis; Students Writing